mTOR signaling in hair follicle and hair diseases: recent progress - Tu, Wei; Cao, Yu-Wei; Sun, Mang; Liu, Qian; Zhao, Heng-Guang (Frontiers in Medicine, 2023)
Mammalian target of rapamycin (mTOR) signaling pathway is a major regulator of cell proliferation and metabolism, playing significant roles in proliferation, apoptosis, inflammation, and illness. More and more evidences showed that the mTOR signaling pathway affects hair follicle circulation and maintains the stability of hair follicle stem cells. mTOR signaling may be a critical cog in Vitamin D receptor (VDR) deficiency-mediated hair follicle damage and degeneration and related alopecia disorders. This review examines the function of mTOR signaling in hair follicles and hair diseases, and talks about the underlying molecular mechanisms that mTOR signaling regulates.